Effect of dietary protein on reproductive growth of Khaki Campbell ducks - GIRI, S C; SAHOO, S K; SASTRY, K V H; BAIS, R K S (The Indian Journal of Animal Sciences, 2015)
A study was carried out to find out the minimum level of crude protein in grower diet of female ducks between 8-16 weeks of age for optimum growth of reproductive organs and earliest onset of egg laying. Khaki Campbell ducklings (420) were brooded and maintained with starter ration till 8 wks of age after which 180 female ducks were randomly selected and reared in 3 groups with 3 replicates in each. Three types of iso-caloric grower ration (14, 16 and 18% crude protein) were offered separately between 8-16 wks of age. At 12th and 16th wk of age, biometry of female reproductive tract was taken. Total protein, total cholesterol, calcium and inorganic phosphorus level in blood serum at 12 and 16 wks age and age at first egg were recorded. The observations revealed the maximum growth of female reproductive organs took place between 12-16th wk age. Significant differences were found in length of whole reproductive tract, infundibulum and weight of ovary between 3 feeding groups at 12th wk of age and width of ovary at 16th wk. Age at first egg was the lowest for 16% CP followed by 18 and 14% fed group. Concentration of total protein at 12 and 16 wks and calcium at 16th wk age differed significantly between groups. Thus, It may be concluded that 16% CP in diet is beneficial for Khaki Campbell ducks during growing stage for better reproductive organ growth as well as for early sexual maturity.